2012
DOI: 10.1111/j.1440-0960.2011.00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Porokeratosis in Singapore: An Asian perspective

Abstract: Porokeratosis is a rare disorder of skin keratinisation characterised by a cornoid lamella. We reviewed its associations with immunosuppression and phototherapy, as well as the risks of malignant progression. This is a retrospective review on all cases of porokeratosis seen at the National Skin Centre, Singapore, between 2000 and 2010. A total of 94 patients were reviewed. Clinical and histological diagnoses were confirmed in 63% patients. Most patients were Chinese (89%) with a mean age of 51.6 years. The mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 7 publications
(6 reference statements)
0
13
0
2
Order By: Relevance
“…Medications, used for the treatment of actinic keratosis, such as 5-fluorouracil, diclofenac gel 3%, imiquimod, retinoid and ingenol mebutate, or topical glucocorticoids could be suggested, but all show a limited effect [8] . In a retrospective study of Tan and Chong [9] , a good response was achieved in only 15 and partial response in 53 of 94 patients, treated with various methods and for any type of porokeratosis. Larger areas of DSAP could be treated with PDT, but conventional PDT is a painful treatment option and shows conflicting results [10] , whereas daylight PDT is a better tolerated option and has demonstrated a positive effect in 2 patients [11] , but further investigations are needed.…”
Section: Resultsmentioning
confidence: 99%
“…Medications, used for the treatment of actinic keratosis, such as 5-fluorouracil, diclofenac gel 3%, imiquimod, retinoid and ingenol mebutate, or topical glucocorticoids could be suggested, but all show a limited effect [8] . In a retrospective study of Tan and Chong [9] , a good response was achieved in only 15 and partial response in 53 of 94 patients, treated with various methods and for any type of porokeratosis. Larger areas of DSAP could be treated with PDT, but conventional PDT is a painful treatment option and shows conflicting results [10] , whereas daylight PDT is a better tolerated option and has demonstrated a positive effect in 2 patients [11] , but further investigations are needed.…”
Section: Resultsmentioning
confidence: 99%
“…This is in concordance with study done by Hegde et al, which showed presence of amyloid in the dermis in cases of lichen amyloidosis. 5,14,15 Subepidermal bullae formation was seen in a case of bullous lichen planus. This finding is supported by various studies which have shown presence of subepidermal bulla in bullous lichen planus.…”
Section: Pattern Of Inflammatory Infiltratesmentioning
confidence: 99%
“…According to previous studies, PM is usually confined to the four limbs (25). However, in the cases included the present study, the initial region was primarily the buttock and genital area.…”
Section: Discussionmentioning
confidence: 99%